Analisis Penerimaan Sistem Informasi Pada Rumah Sakit Umum Daerah Sidoarjo - A’yun, Ainul Fithrotul; Suharso, Wildan; Wahyuni, Evi Dwi (STIKOM Tunas Bangsa Pematangsiantar, 2018)
Information systems become an important part in all areas of life, one of which is a hospital that uses information systems as a support for business processes. The level of user acceptance of the information system in the hospital needs to be reviewed and analyzed as a way to improve service because the main factors that play an important role are users. This study analyzes the factors that influence the acceptance of users of information using the TAM (Technology Acceptance Model). This study uses employee data as a sample, 30 respondents used to test the validity and reliability, from the number of 1436 employees used 112 respondents and the questionnaire returned was 94 questionnaires. Determination of the number of respondents based on Slovin formula shows the number used is 94 respondents. The research methodology includes literature study, determination of research variables, data collection and observation, hypothesis determination, instrument development, questionnaire distribution, data processing and analysis of results. In the development of instruments found 6 variables with 32 indicators, and 35 question items. Based on the validity test found 5 indicators that are not used and Cronbach's alpha value of 0.912 which means that the value is greater than 0.6 so that the instrument is reliable. Research shows that the correlation of the final results shows that the significance level is below 0.05 and shows that the independent variables have a significant influence on the dependent variable, so it can be concluded that user acceptance of the technology in Sidoarjo Regional General Hospital is good.